2019
DOI: 10.1155/2019/7260851
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Heavy Metal Ions Chelating Properties of Multifunctional Polymer-Grafted Silica Hybrid Materials

Abstract: In this research work, novel hybrid materials based on multifunctional polymers and silica were developed and investigated in view of possible employment as sorbents for removal of heavy metal ions from water in presence of various ions. Organic-inorganic hybrid materials were prepared by covalent bonding of vinyl-terminated polyamidoamine (PAA) onto aminated silica particles. Two series of polyamidoamine-grafted silica, differing in the PAA chemical structure, were synthesized, and their heavy metal ions chel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In addition to the sorbent cases mentioned in Table 2 , our preliminary findings with the new melanin nanoparticles show better removal rates for Cu 2+ , Ni 2+ and Zn 2+ compared to other sorbents, such as polymer-grafted silica systems. 27 In all literature cases examined, we observed that melanin nanoparticles exhibit significantly higher removal capacity of Zn 2+ ions.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition to the sorbent cases mentioned in Table 2 , our preliminary findings with the new melanin nanoparticles show better removal rates for Cu 2+ , Ni 2+ and Zn 2+ compared to other sorbents, such as polymer-grafted silica systems. 27 In all literature cases examined, we observed that melanin nanoparticles exhibit significantly higher removal capacity of Zn 2+ ions.…”
Section: Resultsmentioning
confidence: 58%
“…19 The most common adsorption methods are adsorption on activated carbon, [20][21][22] as well as on natural or synthetic polymers. [23][24][25][26][27] Inexpensive powders and natural feedstocks and waste products have also been used in adsorption methods either as such or after conversion to activated carbons. 25 Melanins are a family of polymeric bio-pigments found in many parts of the human body including the hair, skin, and eyes, [28][29][30] and are known to bind a variety of inorganic and organic species.…”
Section: Introductionmentioning
confidence: 99%
“…The dark colour of the oil causes the level the clarity of the oil to be very low, and this is due to its high iron content [ [13], [14]] argues that contamination by iron occurs during the distillation process which uses a metal iron distiller. Iron ions can stimulate oxidation reactions in conjugated double bonds found in patchouli alcohol compounds in patchouli oil to produce colour-forming chromophore compounds from groups >C=C< or >C=C [15].…”
Section: Resultsmentioning
confidence: 99%
“…The rapidly increasing global population, along with the development of industrialization, has triggered various environmental issues in many countries worldwide. Heavy metal (HM) in wastewater has emerged as a global environmental concern because of its adverse effects on human beings and ecosystems [1]. Among the HMs commonly found in wastewater, hexavalent chromium (Cr(VI)) is considered as one of the most harmful and toxic metal forms because of its high carcinogenic and mutagenic properties [2,3].…”
Section: Introductionmentioning
confidence: 99%